2013
DOI: 10.5120/13156-0839
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cluster Partition in Principal Component Analysis Guided Clustering

Abstract: Principal component analysis (PCA) guided clustering approach is widely used in high dimensional data to improve the efficiency of K-means cluster solutions. Typically, Pearson correlation is used in PCA to provide an eigenanalysis to obtain the associated components that account for most of the variations in the data. However, PCA based Pearson correlation can be sensitive on non-Gaussian distributed data, which involve skewed observations such as outlying values. Thus, applying PCA based Pearson correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The algorithm of SVM has been proven effectively to be used in regression and classification methods. Based on previous studies from [19], the study reported that the SVM is generally able to result the best accuracy of classification compare than other methods. Also, SVM can performs linear and nonlinear classification with high efficiently.…”
Section: B Support Vector Machine (Svm)mentioning
confidence: 99%
“…The algorithm of SVM has been proven effectively to be used in regression and classification methods. Based on previous studies from [19], the study reported that the SVM is generally able to result the best accuracy of classification compare than other methods. Also, SVM can performs linear and nonlinear classification with high efficiently.…”
Section: B Support Vector Machine (Svm)mentioning
confidence: 99%
“…The PCA was carried out with the software Statistica 7.0. PCA was used to reveal interrelationships among the ten species of the genus Beilschmiedia based on the essential oil common constituents of these species (Wickramagamage, 2010;Shaharudin et al, 2013;Shaharudin et al, 2018).…”
Section: Multivariate Data Analysismentioning
confidence: 99%
“…The PCA was carried out with the software Statistica 7.0. PCA was used to reveal interrelationships among the ten species of the genus Goniothalamus based on the essential oil common components of these species (Wickramagamage, 2010;Shaharudin et al, 2013Shaharudin et al, , 2018.…”
Section: Speciesmentioning
confidence: 99%